Aeromedical psychology - Kennedy, Carrie H.; Kay, Gary G. (Burlington, Vt. : Ashgate, 2013)
"Aeromedical Psychology provides the means for a variety of clinicians to carry out sound assessment and selection procedures, perform informed evaluations and make subsequent recommendations regarding flight status and treatment strategies geared to the aviation environment. To facilitate a dynamic understanding of the field, the book emphasizes an integration of applications and theory, case examples and research"-Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Aviation psychology; Flight crews -- Psychology; Electronic books